On the long-term behaviour of the performance-potential-metamodel PerPot: New results and approaches - Perl, J. (International Journal of Computer Science in Sport, 2003)
The Performance-Potential-Metamodel PerPot has been developed in order to describe and analyse phenomena of physiological adaptation. It turned out that those adaptation processes depend fundamentally on delays, which characterize the time dependent behaviour of production and transport in respectively between physiological components.